Penguatan Wawasan Pluralisme: Pendidikan Aswaja pada Mahasiswa di Universitas Pesantren Tinggi Darul Ulum Jombang - Fandy Ahmad (DIDAKTIKA, 2025)
This research aims to explore the insight of pluralism in Aswaja education and reveal the process of Aswaja education for students at Darul Ulum Jombang Higher Islamic Boarding University. Using qualitative methods, data were collected through observation and interviews with leaders, lecturers, and students, then the data were analysed thematically. The findings related to the exploration of pluralism insights in Aswaja education, reveal that the education is delivered through Aswaja and Ke-Darul Ulum-an courses, there are 6 aspects of pluralism insights in learning materials, namely (1) Creating relationships that understand and respect each other, (2) Accepting differences and diverse opinions, (3) Resolving conflicts with dialogue and cooperation, (4) Avoiding unfair attitudes and discrimination, (5) Willing to learn new things and adjust, (6) Being inclusive and prioritising unity. Then related to the process of Aswaja education in students, it was revealed that Aswaja education became the basis of thought and practice for students to be pluralistic in dealing with societal differences. They have been taught to understand Islamic teachings with a balance of religious values and social conditions. Then they are also trained to always look at various points of view before making decisions so that a fair and welfare solution is born. Learning about the various madhhabs in Islam is a major aspect, by understanding the background of each madhhab, it will understand the reasons behind the differences. This not only strengthens students' insights but also trains them to critically analyse the diversity of Islam that exists today.